2016
DOI: 10.1007/s12020-016-0991-9
|View full text |Cite
|
Sign up to set email alerts
|

The role of core-needle biopsy in the diagnosis of thyroid malignancy in 4580 patients with 4746 thyroid nodules: a systematic review and meta-analysis

Abstract: To evaluate the effectiveness and complications of core-needle biopsy (CNB) compared to fine-needle aspiration (FNA) for diagnosing thyroid malignancy. The Ovid-MEDLINE and EMBASE databases were searched for studies using CNB for diagnosing thyroid malignancy. A meta-analysis was performed to evaluate the diagnostic accuracy, the incidence of non-diagnostic, inconclusive results, and the complications of CNB and FNA. To overcome the heterogeneity, additional analyses based on three, homogeneous inclusion crite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
30
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 60 publications
(119 reference statements)
2
30
1
3
Order By: Relevance
“…In a meta-analysis by Suh et al (95), both CNB and FNA showed high specificity (99% vs. 100%) for the diagnosis of thyroid malignancy. However, CNB demonstrated a significantly lower pooled proportion of non-diagnostic (5.5%, p < 0.001) and inconclusive (8.0%, p < 0.001) results than FNA (22.6% and 40.2%, respectively) and higher sensitivity (91% vs. 74%, p = 0.053).…”
Section: Clinical Outcomesmentioning
confidence: 97%
See 1 more Smart Citation
“…In a meta-analysis by Suh et al (95), both CNB and FNA showed high specificity (99% vs. 100%) for the diagnosis of thyroid malignancy. However, CNB demonstrated a significantly lower pooled proportion of non-diagnostic (5.5%, p < 0.001) and inconclusive (8.0%, p < 0.001) results than FNA (22.6% and 40.2%, respectively) and higher sensitivity (91% vs. 74%, p = 0.053).…”
Section: Clinical Outcomesmentioning
confidence: 97%
“…Regarding the diagnostic accuracy of thyroid malignancy, a meta-analysis by Suh et al (95) compared the results of 12 CNB studies (2122454756575969859699100) with those of 6 FNA studies (224556575996). The specificities of both CNB and FNA were very high (both 99.5%) but the sensitivity was higher for CNB (74% [95% confidence interval, 67–81%] vs. 50% [95% confidence interval, 44–56%]).…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…The current strategy for non-diagnostic FNA results for nodules that are suspicious on ultrasound (US), is not to operate immediately, but to repeat the FNA within a month. Another interesting finding of the above study was the low specificity of FNA, although it has been reported above 85% in multiple recent studies [2].…”
mentioning
confidence: 50%
“…Currently percutaneous FNA is often performed for cancer diagnosis in various solid organs, such as breast, liver, and thyroid gland as well as in accessible lymph nodes [18]. FNAs are much easier to perform than core needle biopsies and are associated with significantly fewer complications.…”
Section: Discussionmentioning
confidence: 99%
“…FNAs are much easier to perform than core needle biopsies and are associated with significantly fewer complications. A recent metaanalysis of more than 4500 patients undergoing core-needle biopsy and/or FNA for thyroid cancer diagnosis reported an essentially 0 % complication rate [18]. In addition, cessation of oral anticoagulation or anti-platelet agents might not be necessary before fine needle aspiration [19, 20].…”
Section: Discussionmentioning
confidence: 99%